Zarządzanie uwagą na lekcji języka obcego w fazie percepcji i przetwarzania struktur językowych - Kubiczek, Agnieszka (Neofilolog, 2010)
This paper focuses on the connection between cognitive psychology and foreign language pedagogy in the context of perception and processing of language structures. It describes second language acquisition as the processing of language information, which is influenced by attention focused on language data. The concept of instructed learning assumes the possibility of manipulating learners’ attention by the teacher. The paper provides a theoretical background referring to such issues and also examples of how this kind of knowledge can be used in the classroom.